Effect of tertiarybutylhydroquinone on lipid oxidation in fish crackers - Ahmad, Shamsuddin; Augustin, M.A. (1985)
The effect of tertiarybutylhydroquinone (TBHQ) in retarding lipid oxidation in fish crackers fried in refined, bleached and deodorised palm olein (RBD olein) during storage was evaluated. The indices of lipid oxidation used were the peroxide and p‐anisidine values and u.v. absorbances at 232 and 268 nm of oil extracted from fish crackers stored at 60°C. Two methods for TBHQ incorporation into the fish crackers were used. Fish crackers that were prepared by frying of fish chips in RBD olein containing TBHQ were more stable towards oxidative rancidity than control fish crackers prepared with RBD olein without TBHQ. The rate of lipid oxidation in fish crackers prepared from fish chips that were made with TBHQ in the dough formulation and fried in RBD olein without TBHQ was slightly higher than in control fish crackers. A storage study carried out at room temperature (30°C) showed the same trend in relative rates of lipid oxidation. The study showed that the incorporation of TBHQ into the frying medium was an effective means of retarding the onset of rancidity in fried fish crackers while the incorporation of TBHQ into the dough mixture made the fish cracker slightly more susceptible towards lipid oxidative reactions. Copyright © 1985 John Wiley & Sons, Ltd